Spatial bandwidth-optimized compression of image plane off-axis holograms with image and video codecs - Stępień, P.; Muhamad, R. K.; Blinder, D.; Schelkens, P.; Kujawińska, M. (Optics express, 2020)
Image plane off-axis holograms (IP-OAH) are the most common data captured in digital holographic microscopy and tomography. Due to increasing storage and data transmission requirements, lossy compression of such holograms has been subject of earlier investigations. However, hologram compression can not be allowed to hinder the metrological capabilities of the measurement technique itself. In this work, we present lossy and lossless IP-OAH compression approaches that are based on conventional compression codecs, but optimized with regard to bandwidth of the signal. Both approaches outperform respective conventional codecs, while the lossy approach is shown to uphold the accuracy of holographic phase measurements.